Taxonomic revision of the Afrotropical hover fly genus Senaspis Macquart (Diptera, Syrphidae) - Meyer, M. de; Goergen, Georg E.; Jordaens, K. (Pensoft Publishers, 2020)
The representatives of the Afrotropical hover fly genus Senaspis Macquart (Diptera) are revised. In total, ten species are recognized. Senaspis apophysata (Bezzi) is herewith placed as junior synonym of S. flaviceps Macquart, S. livida (Bezzi) is herewith placed as junior synonym of S. dentipes (Macquart) and S. griseifacies (Bezzi) is herewith placed as junior synonym of S. haemorrhoa (Gerstaecker). All species are redescribed and an identification key is provided. DNA barcoding analysis (7 species, 64 barcodes) showed that the technique can be used to unambiguously identify the species. The relationships among the different Senaspis species are discussed based on morphological and DNA data.